2019
DOI: 10.1080/15548627.2019.1586248
|View full text |Cite|
|
Sign up to set email alerts
|

SIGMAR1/Sigma-1 receptor ablation impairs autophagosome clearance

Abstract: Autophagosome-lysosome fusion is a common critical step in various forms of macroautophagy/autophagy including mitophagy, the selective degradation of mitochondria. Regulations of this fusion process remain poorly defined. Here we have determined the role of SIGMAR1, a unique endoplasmic reticulum membrane protein. Knockout of Sigmar1 impaired mitochondrial clearance without altering the PINK1-PRKN/Parkin signaling, in mouse retinal explants and cultured cells treated with carbonyl cyani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 68 publications
0
44
1
Order By: Relevance
“…where damaged mitochondria are degraded by hydrolases. 4,64 As such, disturbed lysosomal function or impaired mitophagosome-lysosome fusion can alter mitophagic flux outcomes. 6 Here, we found that mitophagic flux blockade resulted from impairments in mitophagosome-lysosome fusion and lysosomal degradation ability in compression-exposed human NP cells.…”
Section: Discussionmentioning
confidence: 99%
“…where damaged mitochondria are degraded by hydrolases. 4,64 As such, disturbed lysosomal function or impaired mitophagosome-lysosome fusion can alter mitophagic flux outcomes. 6 Here, we found that mitophagic flux blockade resulted from impairments in mitophagosome-lysosome fusion and lysosomal degradation ability in compression-exposed human NP cells.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy plays an important role in cardiac fibrosis, as well as in other fibrotic diseases [ 50 ]. Zhang et al [ 51 ] reported that the tribbles pseudokinase 3 (TRIB3) mediates autophagy impairment by not only suppressing autophagic degradation but also promoting the activation of hepatic stellate cells (HSCs).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, loss-of-function mutations and Sig-1R deficiency are associated with defective autophagy, leading to accumulation of autophagic vacuoles. In contrast, reexpressing Sig-1R in the null background or its activation restores/induces autophagic activity (Vollrath et al, 2014;MacVicar et al, 2015;Christ et al, 2019;Yang et al, 2019;Christ et al, 2020). Sig-1R is not likely a core component of the general physiological autophagy machinery but it seems needed for cellular stress-induced autophagy (MacVicar et al, 2015).…”
Section: Intreraction With Master Unfolded Protein Response Regulatorsmentioning
confidence: 99%